Feasibility of training athletes for high-pressure situations using virtual reality - Stinson, C.; Bowman, D.A. (IEEE Transactions on visualization and computer graphics, 2014)
Virtual reality (VR) has been successfully applied to a broad range of training domains; however, to date there is little research investigating its benefits for sport psychology training. We hypothesized that using high-fidelity VR systems to display realistic 3D sport environments could trigger anxiety, allowing resilience-training systems to prepare athletes for real-world, high-pressure situations. In this work we investigated the feasibility and usefulness of using VR for sport psychology training. We developed a virtual soccer goalkeeping application for the Virginia Tech Visionarium VisCube (a CAVE-like display system), in which users defend against simulated penalty kicks using their own bodies. Using the application, we ran a controlled, within-subjects experiment with three independent variables: known anxiety triggers, field of regard, and simulation fidelity. The results demonstrate that a VR sport-oriented system can induce increased anxiety (physiological and subjective measures) compared to a baseline condition. There were a number of main effects and interaction effects for all three independent variables in terms of the subjective measures of anxiety. Both known anxiety triggers and simulation fidelity had a direct relationship to anxiety, while field of regard had an inverse relationship. Overall, the results demonstrate great potential for VR sport psychology training systems; however, further research is needed to determine if training in a VR environment can lead to long-term reduction in sport-induced anxiety.